2020
DOI: 10.1021/acsomega.9b03574
|View full text |Cite
|
Sign up to set email alerts
|

Potential Anti-Tumor Drug: Co-Crystal 5-Fluorouracil-nicotinamide

Abstract: 5-Fluorouracil-nicotinamide (5-FU-NCM), a co-crystal with a 2D layer structure formed by hydrogen bonds, was synthesized by solvent evaporation and liquid phase-assisted grinding at room temperature. Compared to 5-FU alone, the results of solubility, oil−water partition coefficient, anti-tumor effect in vivo and vitro, acute toxicity, and pharmacokinetic parameters indicate that the co-crystal is a potential anti-tumor drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Figure a displays the cumulative amount of ABC and its salt/cocrystals permeated in 480 min, which followed the order ABC-GLA (22.97 mg cm –2 ) > ABC-OXA (22.01 mg cm –2 ) > ABC-AZA (21.14 mg cm –2 ) > ABC-SUA (16.92 mg cm –2 ) > ABC (6.17 mg cm –2 ) . In comparison with ABC, the cumulative amounts of ABC-GLA, ABC-OXA, ABC-AZA, and ABC-SUA permeated increased by 272%, 256%, 242%, and 174%, respectively, indicating that the formation of the salt and cocrystals could effectively improve the permeability of ABC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a displays the cumulative amount of ABC and its salt/cocrystals permeated in 480 min, which followed the order ABC-GLA (22.97 mg cm –2 ) > ABC-OXA (22.01 mg cm –2 ) > ABC-AZA (21.14 mg cm –2 ) > ABC-SUA (16.92 mg cm –2 ) > ABC (6.17 mg cm –2 ) . In comparison with ABC, the cumulative amounts of ABC-GLA, ABC-OXA, ABC-AZA, and ABC-SUA permeated increased by 272%, 256%, 242%, and 174%, respectively, indicating that the formation of the salt and cocrystals could effectively improve the permeability of ABC.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, permeability is positively correlated with lipophilicity. Therefore, the partition coefficients of ABC and its salt/cocrystals were determined, 67 (calculation details and results are given in Table S15). The order of the partition coefficient (log P) at pH 6.8 and 298.15 K was ABC-AZA (−1.01) > ABC-SUA (−1.03) > ABC (−1.06) > ABC-OXA (−1.13) > ABC-GLA (−1.16), indicating that the improvement in the permeability of ABC-AZA and ABC-SUA was related to their increased lipophilicity, while the permeability of ABC-OXA and ABC-GLA could be influenced by other factors.…”
Section: Powder Dissolutionmentioning
confidence: 99%
“…It was shown that the 5-FU-nicotinamide co-crystal had enhanced inhibitory activity and better anticancer effect in comparison to 5-FU. The authors attributed this decrease to be possibly from nicotinamide possessing antioxidant activity Lastly, a conclusion was made that 5-FU-nicotinamide had enhanced solubility compared to the 5-FU alone, the logP value of 5-FU was higher than that of the co-crystal [61]. This showed that the co-crystal was more hydrophilic and had lower membrane permeability than the API.…”
Section: Anticancer Api Co-crystalsmentioning
confidence: 99%
“…A summary of available co-crystals, their composition, indication and status as depicted in Table 4. Formulations such as Suglat ® (Ipragliflozin L-Proline) (Astellas Pharma and Kotobuki Pharmaceutical, Japan), Entresto ® (sacubitril and valsartan) (Novartis, Switzerland), Steglatro ® (ertugliflozin) (Merck Sharp and Dohme B.V, Netherlands), and Steglujan ® (ertugliflozin and sitagliptin) (Pfizer, USA) were marketed between the years 2014 to 2017 [61,97]. Some products were identified as co-crystals at a later stage, while already being on the market, such as Lexapro ® (Escitalopram oxalate oxalic acid) (Lundbeck, Denmark) and Beta-chlor ® (Chloral hydrate and betaine) (Franklin Laboratories, India) [26,60,101].…”
Section: Regulatory Limitations Of Crystalline Productsmentioning
confidence: 99%
“…Cocrystals are orderly arranged multicomponent crystals composed of two or more neutral molecules at fixed stoichiometric ratios through various noncovalent interactions, such as hydrogen-bonding, π-stacking, and halogen-bonding interactions etc. The formation of cocrystals provides an effective way to tailor the physicochemical properties of a given compound at the molecular level, and this strategy has been widely applied to pharmaceuticals. Recently, charge transfer (CT) cocrystals, within which the donor (D) and acceptor (A) are combined by charge transfer interactions, have offered an opportunity to alter the optical properties of organic chromophores in the solid state. In this context, the donor refers to an organic electron-rich molecule, and the acceptor is an organic electron-deficient molecule. CT cocrystals offer an excellent platform for the production of novel solid-state luminescent materials, which are otherwise hard to realize in a single-component system.…”
Section: Introductionmentioning
confidence: 99%